Total quality management and educational innovation in primary and secondary education: A systematic literature review with implications for STEM schooling - Theodoropoulou, Eleni; Psomas, Evangelos; Bouranta, Nancy (American Journal of STEM Education, 2026)
This systematic review examines Total Quality Management (TQM) and educational innovation in primary and secondary education (P&SE). Following PRISMA, 30 Scopus-indexed studies were selected and synthesized through affinity diagramming and thematic analysis. Six interlinked themes emerged: school leadership, stakeholder collaboration, technology adoption, quality assurance, teacher development, and school policy. Quality assurance and school leadership appeared most often; the remaining themes worked as supporting conditions. The review proposes a TQM-Driven Educational Innovation Model and discusses what the findings mean for STEM schooling, where strong quality cultures, inquiry-based teaching, and shared leadership are especially important. The paper offers practical guidance for school leaders and policymakers, with particular attention to the conditions that help STEM-related reforms last over time.